Incidence and Complications of Emergency Peripartum Hysterectomy: A Retrospective Study at Maternal and Child Health Training Institute, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Emergency peripartum hysterectomy (EPH) is a major surgical venture performed in the setting of life threatening hemorrhage during or immediately after abdominal and vaginal deliveries. In developing countries, 8-10% of maternal mortality directly occurs due to massive obstetrical hemorrhage. Most common indication for emergency peripartum hysterectomy has been uterine atony and uterine rupture. The decision to perform an emergency hysterectomy on a young woman especially one with low parity poses a dilemma for the obstetrician particularly in our society.Objective: To estimate incidence, indications and postoperative complications associated with emergency hysterectomy at Maternal and Child Health Training Institute (MCHTI), Azimpur, Dhaka.Materials and Methods: This is a retrospective study and registration numbers of all women who underwent emergency peripartum hysterectomy were indentified. With the numbers, the case notes were retrieved from the medical records department for in-depth study. Information abstracted included the socio-demographic characteristics of the patients, indications for the hysterectomy, type of hysterectomy performed, booking status of patients, mode of delivery, gestational age at delivery and maternal outcome were recorded in a pre-designed data form. The data were analyzed using simple proportion, rates and tables.Results: There were 18 cases of emergency peripartum hysterectomies performed during the study period of January 2011 to December 2013 (incidence 1.26/1000 deliveries). Commonest age of the middle group was 29-34 years. Ruptured uterus was the commonest indication (9 cases, 50%) and other indications were uterine atony/ PPH (8 cases, 44.44%), placenta praevia (1 case, 5.56%). Subtotal abdominal hysterectomy was done in 17(94.44%) cases whereas total abdominal hysterectomy in 01(5.56%) cases. This emergency procedure was associated with significant number of intraoperative and postoperative complications, However maternal and perinatal outcome was satisfactory.Conclusion: EPH remains an essential life saving procedure and its incidence continues to remain high in our community when compared with developed countries. Effective antenatal care, identification of patients at risk, enhancement of blood transfusion facilities together with improvement of surgical skills are important to reduce the incidence of peripartum hysterectomy as well as morbidity and mortality.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 106-110